Whole blood transcriptomics analysis of Indonesians reveals translocated and pathogenic microbiota in blood - Katalina Bobowik; Muhamad Fachrul; Chelzie Crenna Darusallam; Pradiptajati Kusuma; Herawati Sudoyo; Clarissa A. Febinia; Safarina G. Malik; Christine A. Wells; Irene Gallego Romero (PLoS ONE, 2025)
Pathogens found within local environments are a major cause of morbidity and mortality. This is particularly true in Indonesia, where infectious diseases such as malaria or dengue are a significant part of the disease burden. Unequal investment in medical funding throughout Indonesia, particularly in rural areas, has resulted in under-reporting of cases, making surveillance challenging. Here, we use transcriptome data from 117 healthy individuals living on the islands of Mentawai, Sumba, and the Indonesian side of New Guinea Island to explore which pathogens are present within whole blood. We identified diverse microbial taxa in RNA-sequencing data from whole blood but found no evidence of a consistent core microbiome across the Indonesian cohort. Yet, Flaviviridae and Plasmodium stood out as the most predominantly abundant taxa, particularly in samples from the easternmost island within our Indonesian dataset. The high prevalence of Plasmodium, the pathogen responsible for malaria, aligns with epidemiological data showing that the Indonesian part of New Guinea has the country’s highest malaria rates. We also compare the Indonesian data to two other cohorts from Mali and UK and find a distinct microbiome profile for each group. Higher levels of dissimilarity were found between UK cohort (urban) compared to Indonesian and Malian cohorts (rural), where the former also have significantly lower within-population dissimilarity. This study provides a framework for RNA-seq as a possible retrospective surveillance tool and an insight to what makes up the transient human blood microbiome.